Psychological characteristics of participants’ behavior management in modeling experiments - Hovhannisyan, Sahak; Lokyan, Arsen (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
Modeling experiments have increasingly become vital tools for studying human behavior and psychological dimensions. In such research, it is crucial to consider not only the objective data but also the psychological state, behavioral expressions, and motivations of the participants. It is hypothesized that the effective management of participants’ behavior and motivation in modeling experiments enables the acquisition of more accurate and reliable results while reducing the likelihood of obtaining disconnected, false data caused by participants’ lack of interest or stress. This article examines the psychological characteristics of individuals involved in modeling experiments and approaches to managing their behavior.